Improving Students’ Critical Thinking Skills Using Student Activity Sheet with Assessment for Learning Approach on Colligative Properties of Solutions - M. Hafidz Nasrulloh; Muchlis; Maharani Agustina Arivi (Universitas Syiah Kuala, 2026)
Critical thinking skills (CTS) are a crucial 21st-century skill required in chemistry education. However, many students still have low CTS. One contributing factor is the sub-optimal delivery of feedback by teachers. A pedagogical approach that emphasizes the role of feedback is assessment for learning (AfL). Effective implementation of approach requires instructional tools, such as student activity sheet (SAS), to facilitate both teachers and students during the learning process. This research aims to develop an student activity sheet with AfL approach to enhance students' CTS, specifically within the topic of the colligative properties of solutions. This research employed the Research and Development method with using the 4D model, which was modified into a 3D version (define, design, and develop). The subjects of this research were 36 12th-grade students at SMAN 1 Menganti. The results demonstrate that student activity sheet with AfL approach is valid, as evidenced by a median validation score of ≥ 4 for both content and construct aspects. Furthermore, the student activity sheet is categorized as practical, achieving an observation score of 94.81% and a student response questionnaire score of 89.24%. The developed student activity sheet proven effective in improving students' CTS in colligative properties, as indicated by an N-gain score of 0.73 (high category). Consequently, the student activity sheet with AfL approach has successfully facilitated teachers in implementing the AfL approach to improvement in students' CTS